How Employees Choose their Commuting Transport Mode: Analysis Using the Stimulus-Organism-Response Model - Ludfi Djakfar; Melchior Bria; Achmad Wicaksono (Journal of Advanced Transportation)
Although transport mode choice in commuting from home to work has been studied extensively, no prior research has investigated mode choice as an emotional response to external stimuli using the stimulus-organism-response (SOR) model. Therefore, this study applies the SOR model to explore commuters’ transport mode choice behaviour. The stimulus variables include trip characteristics, transport infrastructure and services, environment, and work characteristics; the organism variable includes the travel experience and attitude of the individual; and the response variables include use of public transport, private transport, and e-hailing. Data were collected using a questionnaire survey of 500 formal-sector workers in Jakarta; 430 respondents provided valid responses for analysis. The survey data were analysed using partial least squares-structural equation modelling. The results showed that the stimulus variables, namely, trip characteristics, transport infrastructure, environment, and work characteristics, had indirect effects on the choice of e-hailing through organism factors (travel experience and attitude). Also, the environment and work characteristic variables had an indirect effect on the choice of private transport through organism factors. Stimulus variables had no indirect effects on public transport usage. When travel experience was the stimulus variable, the indirect effect on public transport usage through attitude as the organism variable was significant. The response to the use of transport modes showed dynamic behaviour, depending on the provided stimulus and organism. These findings can be beneficial for establishing a more comprehensive strategy that includes the provision of infrastructure, improvement of transit service, the built environment, and employers’ policies to realise a sustainable commuting trip.